Exome and Tissue-Associated Microbiota as Predictive Markers of Response to Neoadjuvant Treatment in Locally Advanced Rectal Cancer - Takenaka, Isabella Kuniko T. M.; Bartelli, Thais F.; Defelicibus, Alexandre; Sendoya, Juan M.; Golubicki, Mariano; Robbio, Juan; Serpa, Marianna S.; Branco, Gabriela P.; Santos, Luana B. C.; Claro, Laura C. L.; dos Santos, Gabriel Oliveira; Kupper, Bruna E. C.; et al. (Frontiers in Oncology, 2022)
The clinical and pathological response to multimodal neoadjuvant therapy in locally advanced rectal cancers (LARC) remains unpredictable, and robust biomarkers are still lacking. Recent studies have shown that tumors present somatic molecular alterations related to better treatment response, and it is also clear that tumor-associated bacteria are modulators of chemotherapy and immunotherapy efficacy, therefore having implications for long-term survivorship and good potential as biomarkers of outcome. Here, we performed whole exome sequencing (WES) and 16S rRNA amplicon sequencing from 44 pre-treatment LARC-biopsies from Argentinian and Brazilian patients, treated with neoadjuvant chemoradiotherapy or total neoadjuvant treatment (nCRT), searching for predictive biomarkers of response (responders, n = 17; non-responders, n = 27). In general, the somatic landscape of LARC was not capable to predict response, however, a significant enrichment in mutational signature SBS5 was observed in non-responders (p = 0.0021), as well as the co-occurrence of APC and FAT4 mutations (p < 0.05). Microbiota studies revealed similar alpha and beta diversity of bacteria between response groups. Yet, linear discriminant analysis (LDA) of effect size (LEfSe) indicated an enrichment of Hungatella, Flavonifractor, and Methanosphaera (LDA score ≥ 3) in pre-treatment biopsies of responders, while non-responders had higher abundance of Enhydrobacter, Paraprevotella (LDA score ≥ 3) and Finegoldia (LDA score ≥ 4). Altogether, the evaluation of these biomarkers in pre-treatment biopsies could eventually predict neoadjuvant treatment response, while in post-treatment samples it could help guiding non-operative treatment strategies.